Suppression of pulmonary innate host defence in smokers. Issue 2 (13th October 2008) - Herr, C; Beisswenger, C; Hess, C; Kandler, K; Suttorp, N; Welte, T; Schroeder, J-M; Vogelmeier, C; Group, R Bals for the CAPNETZ Study
Abstract : Background: Smoking increases the susceptibility to pulmonary infection and is a risk factor for the development of chronic obstructive pulmonary disease (COPD). It is postulated that cigarette smoke suppresses the activation of the innate immune system in response to bacterial infection. Methods: Using sensitive ex vivo analysis, the level of the endogenous antibiotic peptide human β-defensin-2 (hBD-2) was measured in pharyngeal washing fluid and sputum from patients with community acquired pneumonia. The regulation of antibacterial host defence molecules was studied in vitro. The effect of cigarette smoke on the antibacterial activity of differentiated airway epithelium and the expression of host defence molecules was studied in an in vitro infection model. Results: Current or former smoking was associated with significantly reduced hBD-2 levels in pharyngeal washing fluid and sputum from patients with acute pneumonia. Exposure of airway epithelium to smoke in vitro inhibited the induction of hBD-2 by bacteria. This correlated with decreased antimicrobial activity. This effect was mimicked by hydrogen peroxide, and catalase blunted the smoke-induced inhibition of epithelial host defence. Conclusions: Smoke exposure suppresses the induction of epithelial antibacterial host defences. These findings link smoking with increased susceptibility to infection. This mechanism may be important in the pathogenesis of pneumonia and COPD.